(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Scaphoid fractures are common in the wrist, but difficulty from soon diagnosis because of the particular geometry of the fractures and the tenuous vascular pattern of them. Delays in diagnosis and inadequate treatment for acute scaphoid fractures can lead to nonunion and subsequent degenerative wrist arthritis. Scaphoid nonunion is defined as a non-healed 6 months after injury. Four-corner fusion with excision of the scaphoid is an accepted procedure for treating scaphoid nonunion advanced collapse (SNAC). Method: Cases study. In Department of Orthopedics, Thong Nhat Dong Nai Hospital, we presented 02 cases scaphoid nonunion, which treated four-corner fusion with excision of the scaphoid using headless compression screw (Herbert crew). Result: 02 cases had good range of motion (ROM) and no pain. Conclusion: Four-corner with excision of the scaphoid is the good method to treat scaphoid nonuion.